POSTWAR INTERNATIONAL ORGANIZATIONS PREDECESSOR OF THE EUROPEAN UNION - Dragoș-Adrian BANTAȘ; Elvira BELDIMAN (Challenges of the Knowledge Society)
The European Union, as its existence that we can meet in the present moment, is not a creation which came out of nothing or arising of the history’s hazard, but is rather an evolutionary process that began after the end of the Second World War. In this respect, in their continuing search for security, cooperation and common prosperity, European countries have made, in turn, organizations with different profiles (economic, political, security), such as the Treaty of Dunkirk, Western Union, Organization Economic Cooperation in Europe, Council of Europe, Western European Union, all of which are creations precursor Union and, before being dissolved as obsolete or being embedded in Cleaned have served the aims of their times, representing evolutionary steps in defining project European.